P459 Looking at the lipids: quality improvement in the NICU. (June 2019) - Moore, Carmel Maria; Duddy, Peter; Doolan, Anne; Miletin, Jan
Abstract : Background and aims: Parenteral nutrition is a vital part of our management of neonates in the NICU. The National Paediatric and Neonatal Parenteral Nutrition Guidelines were introduced in November 2016. The national guidelines recommend checking serum triglyceride levels on day 3–4 and day 5–7 of PN administration, as well as weekly thereafter if stable. We noted that this was not occurring in our unit and so aimed to audit compliance with national guidelines on lipid monitoring in neonates receiving parenteral nutrition in order to target a quality improvement initiative. Methods: This was a retrospective review of all babies on PN for greater than one week. Cases were identified using the PN order database maintained by the pharmacy team. The laboratory system was interrogated to assess if the babies had triglycerides or lipid indexes checked. Results: 20 babies on PN for greater than one week over the past six months. Only 15% of babies (n=3) had any lipid monitoring performed and no babies had been monitored in compliance with the guidelines. Some babies had both lipid index (performed on site) and triglycerides (performed off site, with a varying turnaround time. Conclusion: There is significant room for improvement in our management of lipid monitoring in our NICU and we are going to initiate a quality improvement initiative to improve compliance with the guidelines including education sessions with NICU staff.